Processing and Interpretation of Magnetic and IP-Resistivity Data - Haritha, K. (Bumi Publikasi Nusantara, 2024)
This project focuses on the processing and interpretation of magnetic and IP-resistivity data, which is to understand the subsurface geological structures and identify potential mineral resources. The data acquisition used appropriate geophysical instruments, including data filtering, imaging, inversion, and modeling techniques. The results obtained from the data analysis provide valuable insights into the subsurface geology. The magnetic data interpretation helps in delineating magnetic anomalies associated with different rock types, structural features, and potential mineralization. The IP-resistivity data interpretation aids in understanding the distribution of electrical properties within the subsurface, which can be indicative of lithological variations, fluid content, and potential mineral deposits. Through the integrated interpretation and correlation of magnetic and IP-resistivity data, important subsurface features and their relationships are identified. This information contributes to a better understanding of the geological framework and potential mineral resources in the study area. The findings of this research have implications for mineral exploration and development, as they provide a basis for further investigation and targeted exploration activities in the region. This project contributes to the knowledge base in geophysics and geology. The results enhance our understanding of the subsurface geology and mineral potential, supporting sustainable development and resource management in the area.